Implemetasi Pidana Mati Bagi Koruptor di Tengah Pandemi - Wibisono, Yohanes Adrian; Hutabarat, Rugun Romaida (Dinasti Research, 2025)
Corruption is a crime that is no longer foreign in Indonesia, corruption is usually carried out by officials who have high incomes. Corruption is also often referred to as White Collar Crime. During the Covid-19 pandemic in 2020, the government allocated additional APBN funds totaling 405.1 trillion Rupiah as a step to handle the crisis. The budget allocated for handling Covid-19 is quite large and requires careful supervision in its implementation so that it can be used to handle Covid-19, but the budget issued by the government was used by Juliari P. Batubara for personal gain and intended to enrich himself, therefore Juliari P. Batubara received a sentence of twelve years in prison along with a monetary penalty of five hundred million rupiah. It is stipulated that failure to pay this fine will result in an additional six months of imprisonment. An additional penalty has been imposed on Juliar P. Batubara, requiring the payment of compensation amounting to Rp14,597,450,000.00 (fourteen billion five hundred ninety-seven million four hundred and fifty thousand rupiah).